KOMPENSASI SEBAGAI ALAT PENINGKATAN KINERJA DALAM BINGKAI AGENCY THEORY - Sulistiani, Dwi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Agency theory looked at the relationship between the owner (the principal) and management (agent). Compensation given to overcome problems in the theory of agency, ie the difference between the interests of owners and agents. Compensation system is designed organization aims to motivate employees to improve their performance and retain competent employees. In order to work incentivecompensation, corporate boards must choose a level measurement and precise performance. Performance-based Reward twofold benefit: informing and motivating.The purpose of this paper is to review how compensation as a performance enhancement tool. The research method uses literature study and its conclusions are: 1. The compensation was given to address the problems in the theory of agency (the difference between the interests of owners and agents). 2. The compensation system is designed organization aims to motivate employees toimprove their performance and retain competent employees. 3. To work incentive compensation, corporate boards must choose a level measurement and preciseperformance. The measurement system there are two traditional compensation (use of accounting profit that measure the past) and the stock price (measuring thefuture).